Mountain Wave Induced Polar Stratospheric Cloud Forecasts for Aircraft Science Flights during SOLVE/THESEO 2000 - Eckermann, Stephen D.; Dörnbrack, Andreas; Vosper, Simon B.; Flentje, Harald; Mahoney, M. J.; Bui, T. Paul; Carslaw, Kenneth S. (Weather and Forecasting, 2006)
The results of a multimodel forecasting effort to predict mountain wave–induced polar stratospheric clouds (PSCs) for airborne science during the third Stratospheric Aerosol and Gas Experiment (SAGE III) Ozone Loss and Validation Experiment (SOLVE)/Third European Stratospheric Experiment on Ozone (THESEO 2000) Arctic ozone campaign are assessed. The focus is on forecasts for five flights of NASA’s instrumented DC-8 research aircraft in which PSCs observed by onboard aerosol lidars were identified as wave related. Aircraft PSC measurements over northern Scandinavia on 25–27 January 2000 were accurately forecast by the mountain wave models several days in advance, permitting coordinated quasi- Lagrangian flights that measured their composition and structure in unprecedented detail. On 23 January 2000 mountain wave ice PSCs were forecast over eastern Greenland. Thick layers of wave-induced ice PSC were measured by DC-8 aerosol lidars in regions along the flight track where the forecasts predicted enhanced stratospheric mountain wave amplitudes. The data from these flights, which were planned using this forecast guidance, have substantially improved the overall understanding of PSC microphysics within mountain waves. Observations of PSCs south of the DC-8 flight track on 30 November 1999 are consistent with forecasts of mountain wave–induced ice clouds over southern Scandinavia, and are validated locally using radiosonde data. On the remaining two flights wavelike PSCs were reported in regions where no mountain wave PSCs were forecast. For 10 December 1999, it is shown that locally generated mountain waves could not have propagated into the stratosphere where the PSCs were observed, confirming conclusions of other recent studies. For the PSC observed on 14 January 2000 over northern Greenland, recent work indicates that nonorographic gravity waves radiated from the jet stream produced this PSC, confirming the original forecast of no mountain wave influence. This forecast is validated further by comparing with a ...